Science Communication in a Digital Age: Social Media and the American Fisheries Society. Issue 8 (14th August 2013) - Claussen, Julie E.; Cooney, Patrick B.; Defilippi, Julie M.; Fox, Sarah Gilbert; Glaser, Sarah Michele; Hawkes, Elden; Hutt, Clifford; Jones, Marissa H.; Kemp, Iris M.; Lerner, Aaron; Midway, Stephen R.; Nesbit, Shivonne; et al.
ABSTRACT: Social media platforms are effective tools used to help communicate and increase involvement in cultural, political, and scientific circles. In 2012, an ad hoc committee was established to explore online fisheries science communication and how social media platforms can be utilized by the American Fisheries Society (AFS). A survey was disseminated to all AFS units (chapters, sections, divisions) and student subunits to better understand the current use of social media within the AFS. A relatively high response rate (82%) provided some confidence in the survey results—namely, that nearly 69% or more of units and subunits used social media. Facebook was the dominant platform used (59%; all others < 15%) and almost exclusively (97%) for the purpose of communication. Education, outreach, and member recruitment were other reasons for social media use. Finally, whether units currently use social media or not at all, it was recommended that AFS‐led workshops and assistance would increase the usefulness of social media.